The South African lobby in America: the battle over sanctions - Harning, Jeannie (Rhodes University, Faculty of Humanities, Department of Political Studies, 1994)
The relationship between South Africa and the United States was, historically, quite mutually profitable. The South African government regarded the United States as an ally in the world and sought continued friendship with them. The United States was mildly critical of the South African system of apartheid, but they, however, viewed South Africa as an ally. During the 1980's the relationship between the two countries became strained as the anti-apartheid voices in the United States grew louder and louder. The movement sought to end the atrocities of apartheid and change American foreign policy toward South Africa. The strongest diplomatic means available to them was imposing economic sanctions on South Africa in an attempt to force political change in the country. The anti-apartheid movement lobbied extensively gaining support among the American pub1ic and eventually the U.S. Congress. The sanctions campaign culminated in the enactment of the Comprehensive Anti-Apartheid Act (CAAA) of 1986. Prior to the enactment of the CAAA the South African government and its allies launched their own campaign in an attempt to combat the imposition of sanctions. Lobbying played a key role in the process for those on both sides of the issue. For the anti- apartheid movement, lobbying was effective on the American public and the U.S Congress. For the South African government lobbying was effective on the conservative right wing and President Reagan and his administration.
Keywords: Lobbying -- South Africa|Lobbying -- United States|Economic sanctions, American -- South Africa|South Africa -- Foreign relations -- United States|United States -- Foreign relations -- South Africa